Navigating Personal Health Crises, Imposter Syndrome, Sexual Harassment, Clinical Mistakes and Leadership Challenges: Lessons for Work-Life Wellness in Academic Medicine: Part 3 of 3 : Wellness in Academic Medicine - Barach, Paul; Ahmed, Rami; Agarwal, Gaurava; Olson, Kristine; Welch, Julie; Chernoby, Kimberly; Hein, Christine; Anand, Tanya; Joseph, Bellal; Rosenstein, Donald; Sotto-Santiago, Sylk; Hartsock, Jane; et al. (Kansas Journal of Medicine, 2023)
In this final manuscript of the three-part series, the authors address issues of imposter syndrome, pregnancy, and parental leave, second victim phenomenon, sexual harassment, response to suicide, and managing a budget while advancing diversity, equity, and inclusion. The case scenarios have learners and non-clinicians as their main characters, bringing attention to the cross-cutting nature of the complex issues we see both in and around a career in medicine.